Uma pesquisa sobre a opinião pública sobre incentivos financeiros para doação de óvulos no Brasil - Espirito Santo, E.; Oliveira, J. B A [UNESP]; Petersen, C. G. [UNESP]; Mauri, A. L.; Baruffi, R. L R; Franco, J. G. [UNESP] (My University, 2013)
Objective: The objective of this study was to assess the opinions of the Brazilian population about incentives for oocyte donation. Methods: A cross-sectional descriptive approach was used to consult the Brazilian public. The data collection involved the use of a structured questionnaire about legal and ethical issues surrounding oocyte donation. Individuals were randomly selected from the general population using different e-mail lists. Potential participants were contacted by e-mail and invited to participate in the study by completing an online web survey. Results: A total of 1,565 people completed the survey, including 1,284 women(82%) and 281 men(18%). Among the respondents, 1,309(83.6%) were university graduates, 1,033(66%) had a personal income ≥1,250 US dollars/month, 1,346(86%) considered themselves to be religious and 518 (33.1%) were health professionals. While many participants believed that women may donate their oocytes for altruistic reasons, the majority believed that a lack of oocyte donations is due to the prohibition of payments(64.3%) and that incentives would facilitate the decision to donate oocytes(84.7%). The majority of the participants(65.3%) agreed that a financial incentive(i.e., paying the donor) would be the most practical solution for increasing the number of oocyte donations. These results tended to be independent of gender, age, income, religion, education level and profession. Conclusion: While the Brazilian Federal Council of Medicine prohibits payments for oocyte donation, the majority of study participants had no objection to compensating oocyte donors. Moreover, most of the participants agreed that a financial incentive is the most practical solution to increasing the number of oocyte donations.
A survey on public opinion regarding financial incentives for oocyte donation in Brazil
Keywords: Ethics; IVF; Oocyte donation; Public opinion; Survey; adult; Brazil; cross-sectional study; donor; female; gender; graduate; health practitioner; health survey; human; income; information processing; male; oocyte donation; public opinion; religion; structured questionnaire